2009
DOI: 10.1038/oby.2009.123
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Girls' BMI Across Childhood and Adolescence

Abstract: This study describes qualitatively distinct trajectories of BMI change among girls participating in a longitudinal study of non‐Hispanic, white girls (n = 182) and their parents, assessed at daughters' ages 5, 7, 9, 11, 13, and 15 years. Height, weight, body fat, fasting blood glucose and lipids, blood pressure, waist circumference, and pubertal status were measured, and participants self‐reported dietary, physical activity, and television (TV) viewing patterns. Growth mixture models were used to model heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
127
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 40 publications
15
127
4
Order By: Relevance
“…As time elapses during adolescence, boys and girls normally undergo an initial rapid and consistent linear increase in BMI (Lammi et al 2009;Ventura et al 2009). Our data was able to capture this initial linear growth, suggesting that both the general level and this initial linear growth were highly mediated by genetic influences (65.1-86.5%).…”
Section: Discussionmentioning
confidence: 99%
“…As time elapses during adolescence, boys and girls normally undergo an initial rapid and consistent linear increase in BMI (Lammi et al 2009;Ventura et al 2009). Our data was able to capture this initial linear growth, suggesting that both the general level and this initial linear growth were highly mediated by genetic influences (65.1-86.5%).…”
Section: Discussionmentioning
confidence: 99%
“…BMI [13,14,31,32,33], BMI z-scores [34,35] or BMI percentiles [12,15], and different age ranges. In the case of cutoff points to define overweight, overweight patterns represent a probability of being overweight at a certain time point.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that not all overweight children become overweight adults and not all overweight adults were overweight as a child implies that different longitudinal overweight patterns exist [9,10,11]. Studies have indeed found distinct longitudinal patterns in childhood, among which often a reducing, increasing and persistent overweight pattern is detected [12,13,14]. Different determinants may underlie these longitudinal patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to better understand weight changes and obesity onset in children, growth trajectories have been recommended for tracking overweight longitudinally in youths [5]. In line with that recommendation, most recent studies aiming to understand weight changes in children and adolescents have relied on within-person trajectories obtained from growth mixture modeling [6][7][8][9][10][11][12][13][14][15]. Together, these studies offer an interesting view of weight gain in children and suggest a need to better understand sexual differences and psychosocial predictors of weight changes for preadolescents of all weights and heights.…”
Section: Introductionmentioning
confidence: 98%